The Role of Irisin in Exercise-Mediated Bone Health - Liu, Lifei; Guo, Jianmin; Chen, Xi; Tong, Xiaoyang; Xu, Jiake; Zou, Jun (Frontiers in Cell and Developmental Biology, 2021)
Exercise training promotes physical and bone health, and is the first choice of non-drug strategies that help to improve the prognosis and complications of many chronic diseases. Irisin is a newly discovered peptide hormone that modulates energy metabolism and skeletal muscle mass. Here, we discuss the role of irisin in bone metabolism via exercise-induced mechanical forces regulation. In addition, the role of irisin in pathological bone loss and other chronic diseases is also reviewed. Notably, irisin appears to be a key determinant of bone mineral status and thus may serve as a novel biomarker for bone metabolism. Interestingly, the secretion of irisin appears to be mediated by different forms of exercise and pathological conditions such as diabetes, obesity, and inflammation. Understanding the mechanism by which irisin is regulated and how it regulates skeletal metabolism via osteoclast and osteoblast activities will be an important step toward applying new knowledge of irisin to the treatment and prevention of bone diseases such as osteolysis and other chronic disorders.